Field notes contributed by Marion M. Brewer, winter 1982-1983 - Brewer, Marion M.et al (1982)
Winter report of birds found in and around Cherokee contributed by Marion M. Brewer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed